Regime of protection and use of especially protected natural areas - Zhloba, Albert A. (Journal of the Belarusian State University. Law, 2024)
The article is devoted to legal issues of establishing the regime of protection and use of especially protected natural areas in the Republic of Belarus. The author defines the composition of normative legal acts, enshrining the desired regime. Analysing the current legislation, the author identifies problems and proposes ways to solve them.
Keywords: regime of protection and use; national park; especially protected natural area; protected natural area; environmental protection